Estrategias de prevención para disminuir el consumo de sustancias psicotrópicas heroína (h) en los estudiantes de la Unidad Educativa, Antonio Andrade Fajardo, Cantón Vinces de La Provincia de Los Ríos - Sanchez Velarde, Geomar (2018)
The psychoactive substances heroin is a problem for families and for society in general, since it seems that this addiction is the cause of conflicts that converge in family dysfunctions and affects the educational, with the respective consequences such as: violence, loss of school years, suicides, traffic accidents. People who suffer from this disease, are considered in the social context, by the WHO "World Health Organization" as a family disease, has been the most worrisome. In the present study, the general objective was to determine the prevention strategies in the primary school to reduce the consumption of substance (H) in the students of the Antonio Andrade Fajardo Educational Unit, in the Vinces canton of the Province of Los Ríos. And as specific objectives; Identify high-risk situations, reflect in advance on them and know guidelines for action towards heroin., Analyze the group pressure as a factor favoring the beginning of drug use, promoting a critical attitude towards it., Knowing the physical consequences, psychic and social consequences of heroin use, in the short and long term: that should not go to a state of violence. The present investigative work is of the research type. Exploratory this type of research allowed us to perform the processes of exploration of the different phenomena that were raised in the investigation. Explicative we use to explain the different characteristics of the phenomena raised in the investigation.